Are the enemies of your enemies your friends? Abuse of law and neo-constitutionalism...: Comment on a constitutional reform project - Miranda Reyes, Diego (Derecho Público Iberoamericano, 2020)
In this article we analyze how the introduction of the figure of abuse of the right, of iusprivatista origin, would impact the Chilean Constitution. A constitutional reform project on the matter is studied from a neoconstitutional perspective.